The filmmaker's philosopher : Merab Mamardashvili and Russian cinema - DeBlasio, Alyssa (2019)
Exploring Mamardashvili's extensive philosophical output, as well as a range of recent Russian films, Alyssa DeBlasio reveals the intellectual affinities amongst directors of the Mamardashvili generation - including Alexander Sokurov, Andrey Zvyagintsev and Alexei Balabanov.